2015
DOI: 10.1038/nnano.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dyes align inside carbon nanotubes to yield a large nonlinear optical response

Abstract: Asymmetric dye molecules have unusual optical and electronic properties. For instance, they show a strong second-order nonlinear optical (NLO) response that has attracted great interest for potential applications in electro-optic modulators for optical telecommunications and in wavelength conversion of lasers. However, the strong Coulombic interaction between the large dipole moments of these molecules favours a pairwise antiparallel alignment that cancels out the NLO response when incorporated into bulk mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
148
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(164 citation statements)
references
References 32 publications
12
148
0
Order By: Relevance
“…[43,44] The resulting chirality-sorted nanotube suspension was first dialyzed to 1%wt/V DOC, using a stirred ultrafiltration cell, and subsequently density gradient ultracentrifugation was used to separate the empty and water-filled (6,5) SWCNTs. [48,49] Similar to previous work [13][14][15][16]48, 49] a combination of optical absorption, resonant Raman and PL-excitation spectroscopy was used to asign the composition of each of the fractions, see SM [46] indicating that the amount of filled SWCNTs are negligible in the empty fraction (< 3.7%), while in the PL spectra of the filled fraction a small contribution of empty SWCNTs can be observed, with an amplitude of ∼ 20% of the total PL intensity. For temperature-dependent optical experiments, SWCNTs were drop-cast on quartz substrates, dried and mounted in a Microstat He2 cryostat (Oxford Instruments).…”
supporting
confidence: 78%
See 3 more Smart Citations
“…[43,44] The resulting chirality-sorted nanotube suspension was first dialyzed to 1%wt/V DOC, using a stirred ultrafiltration cell, and subsequently density gradient ultracentrifugation was used to separate the empty and water-filled (6,5) SWCNTs. [48,49] Similar to previous work [13][14][15][16]48, 49] a combination of optical absorption, resonant Raman and PL-excitation spectroscopy was used to asign the composition of each of the fractions, see SM [46] indicating that the amount of filled SWCNTs are negligible in the empty fraction (< 3.7%), while in the PL spectra of the filled fraction a small contribution of empty SWCNTs can be observed, with an amplitude of ∼ 20% of the total PL intensity. For temperature-dependent optical experiments, SWCNTs were drop-cast on quartz substrates, dried and mounted in a Microstat He2 cryostat (Oxford Instruments).…”
supporting
confidence: 78%
“…Molecular confinement inside SWCNTs moreover results in new functionalities such as amphoteric doping [18] or photosensitization [19,20] of the SWCNTs, enhanced stabilities of the encapsulated molecules, [21] and unique molecular order which is only achievable in such quasi-1D nanocavities. [16] Moreover, recent studies [5,22,23] have revealed nearly zero friction for confined water transportation and superior water permeability in CNTs, indicating their potential applciations in efficient desalination and water purifcation devices. [24,25] Both theoretical calculations [4,26] and experiments [13-15, 27, 28] have demonstrated that water molecules can spontaneously enter the smooth, hydrophobic channels of SWCNTs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, advances in the physical information that can be obtained with this technique continue to be made and the level of finesse with which PL spectra can be individualized into single ( n , m ) contributions and analyzed is improving. 2427 Raman spectral mapping may offer an alternative solution in the future but currently suffers from the need for elaborate tunable excitation sources. In addition to that, highly structure-dependent and unknown sensitivity factors exacerbate the interpretation of the measurement data.…”
Section: Introductionmentioning
confidence: 99%